Providing Husband Support Affects Wife's Anxiety Level in Facing Menopause - Sagia, Bunga Anggita (Archives of The Medicine and Case Reports, 2024)
Menopause is a hormonal change experienced by women as they get older. These hormonal changes can cause a variety of physical and psychological symptoms, including anxiety. Husband's support is one factor that can influence a wife's anxiety level in facing menopause. This study aims to determine the effect of providing husband support on wives' anxiety levels in facing menopause. This research uses an analytical survey method with a cross sectional approach. The research sample was 50 women aged 45-55 years who were experiencing menopause. Data was collected using a husband's support questionnaire and an anxiety level questionnaire. The results of the research show that there is a significant relationship between the husband's support and the wife's level of anxiety in facing menopause. The higher the husband's support, the lower the wife's anxiety level. The conclusion of this study shows that husband's support can play a role in reducing wives' anxiety levels in facing menopause.